The effect of amifostine on bacterial translocation after radiation ınduced acute enteritis - Tas,Sukru (2016)
ABSTRACT PURPOSE: To investigate the effects of amifostine on bacterial translocation and overgrowth in colonic flora after acute radiation enteritis in a rat model. METHODS: Thirty-two female Wistar albino rats were divided into four groups: Group-1 (n=8): only normal saline was administered intraperitoneally. Group-2 (n=8): first serum saline was administered intraperitoneally and 30 minutes later 20 Gy radiation was applied to abdominopelvic region. Group-3 (n=8): only amifostine 200 ml/kg was administered intraperitoneally and radiation was not applied. Group-4 (n=8): first amifostine 200 ml/kg was administered intraperitoneally and 30 minutes later 20 Gy radiation was applied to abdominopelvic region. On the 5th day after radiation, samples of mesenteric lymph tissues and cecal contents were taken by laparotomy for microbiological culture. RESULTS: Intraperitoneal amifostine administration significantly decreased the bacterial overgrowth related to radiation in colon but did not significantly decrease the bacterial translocation. CONCLUSİON: Although not providing a full protection on the damaged mucosal barrier, amifostine significantly decreased the bacterial overgrowth in the cecal content after high dose radiation. There is a need to find out appropriate amifostine dose under different radiation applications avoiding bacterial translocation in gastrointestinal system.